2004
DOI: 10.1086/377741
|View full text |Cite
|
Sign up to set email alerts
|

Measles Eradication in the Americas: Progress to Date

Abstract: The region of the Americas has shown extraordinary progress in its fight to interrupt measles transmission. The Pan American Health Organization's recommended strategy includes the following: a 1-time nationwide campaign targeting 1- to 14-year-old children; routine vaccination among 1-year-olds; and nationwide campaigns conducted every 4 years, targeting all 1- to 4-year-olds. Rapid house-to-house monitoring of vaccination and measles surveillance are other essential components of the strategy. During 2001, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…47 African community studies have shown consistently that female mortality is higher than male mortality prior to MV but declines markedly when the children receive MV. 46,48 Hence, it is our prediction that the relative femalemale mortality rate ratio increased in the age group 9-11 months and that the general mortality of children in the age group 9-11 increased relative to the mortality in the age group 12-14 months when the age of measles vaccine was raised from 9 to 12 months of age.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…47 African community studies have shown consistently that female mortality is higher than male mortality prior to MV but declines markedly when the children receive MV. 46,48 Hence, it is our prediction that the relative femalemale mortality rate ratio increased in the age group 9-11 months and that the general mortality of children in the age group 9-11 increased relative to the mortality in the age group 12-14 months when the age of measles vaccine was raised from 9 to 12 months of age.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…These should be implemented every 2-4 years to prevent the build-up of susceptibles [28]. The Pan American Health Organization (PAHO) has successfully implemented SIAs since the 1990 s, which significantly contributed to the elimination of endemic measles in most Latin American countries [29]. The use of SIAs in sub-Saharan African countries has significantly contributed reductions in measles cases and deaths in that region [3,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Before endemic measles virus transmission ended in the Americas in 2002, outbreaks among young adults occurred in Argentina, Bolivia, Brazil, Canada, Venezuela, and the Dominican Republic [15]. Increasing vaccination coverage among children tends to shift the age of infection toward older ages; in recent years, measles outbreaks in other regions have been characterized by cases among older children and young adults [4,[16][17][18].…”
Section: What Are the Causes Of Measles Outbreaks In Settings With Himentioning
confidence: 99%